Long Run Trends in Economic Inequality in Five Countries - A Birth Cohort View - Lars Osberg (Luxembourg Income Study (LIS), 2000)
This paper examines the level and distribution of equivalent after tax, after transfer money income in Canada, the USA, the UK, Germany and Sweden using micro-data from the Luxembourg Income Study from 1969/70 to 1994/95. It concentrates on inequality within and between birth cohorts. At any point in time, less than 11% of aggregate income inequality is due to intergenerational inequality, but the experience of different birth cohorts over the period has varied widely across countries. The five countries studied differ in the trends observed in aggregate income, poverty, polarization and income inequality. In the USA and the UK, the incomes of the top decile of each cohort have risen dramatically, but the incomes of the bottom quintile have stagnated. In Canada and Sweden both the top and bottom deciles of each cohort have experienced similar trends. Germany is an intermediate case. Poverty trends are extremely sensitive to the distribution of the gains from growth - if only 10% of the income gains of the top decile of the UK and the USA had been transferred to the bottom decile, poverty in both countries in 1994/95 would have been substantially lower than in 1979, instead of substantially higher. The basic lesson is the diversity of income distribution trends to be observed in international data - and the consequent diversity of implications for political economy.
Keywords: 330; Einkommensverteilung; Armut; Steuerbelastung; Einkommensumverteilung; Deutschland; Großbritannien; Kanada; Schweden; USA